Use f(x) = 4x − 7 and g(x) = 3 − x2 to evaluate the expression.

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

(a)   

f(g(−2))
 
 

(b)   
g(f(−2))
 
Feb 23rd, 2015

f(g(-2)) 3-(2)^2= 3-4=-1 plug into 1st equation f(-1)=4(-1)-7=28

b. g(f(-2)) 4(-2)-7=-9 plug into the 2nd equation g(-9)=3-(-9)^2=3-81=78

I hope that this is helpful. Please best my answer, if it was helpful. Thanks!



Feb 23rd, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Feb 23rd, 2015
...
Feb 23rd, 2015
Jun 26th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer